The Examination of the Effect of Organization Culture on Organizational Performance: A Case of Public Sector, Jordan - Farhan, Hodifah; Owaidha, Abu; Anuar Azmin, Adi (International Journal of Engineering and Technology, 2018)
The main purpose of this study is to investigate the outcome of organizational culture among top management from the organizational performance. Specifically, it aimed at investigating the effect of organization culture on organizational performance in public sector, Jordan. Past studies on the organizational culture are limited only to the management level employees in the Public-sector so the definite focus of this study is to investigate the role of organizational culture and organizational performance among the top management staff of public sector, Jordan. A total number of 152 questionnaires were gathered through survey questionnaire from top management from the main city of Jordan, Amman. The data analyzes were done by using Smart PLS 3.0. The findings of this study designate a significantly positive relationship between organizational culture and organizational performance. The study provides implications for the top management of public sector, Policymakers, and leaders in the public sector, they encouraging the staff to towards organizational culture for better organizational performance. Results stirred on how organizational culture can be used to manage organization strategically.Â